Solvothermal synthesis of nanoporous TiO2: the impact on thin-film composite membranes for engineered osmosis application - Emadzadeh, D. (Institute of Physics Publishing, 2016)
In the current study, the impact of self-synthesized nanoporous titanium oxide (NT) on the morphology, performance and fouling of a polyamide (PA) thin-film composite (TFC) membrane was investigated when the membrane was applied for engineering osmosis (EO). The nanoporous structure and the spindle-like shape of NT were revealed through transmission electron microscopy (TEM), while the AATPS modification of NT was verified by attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy. The results of x-ray photoelectron spectroscopy (XPS) and x-ray diffraction (XRD) confirmed the presence of modified NT (mNT) in the PA dense active layer of the TFC membrane. The outgrowth of the 'leaf-like' structure, upon mNT loading, at the surface of the PA layer was observed by field-emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM). The TFC membrane prepared with 0.05 wt% mNT loading in the organic phase showed the water flux of 26.4 l m-2 h-1 when tested in the forward osmosis (FO) mode using 0.5M and 10 mM NaCl solution as the draw and feed solution, respectively. Moreover, the TFC-mNT membrane also demonstrated an intensified antifouling property against organic foulant during FO application and it was possible to retrieve the initial water flux almost completely with a simple water-rinsing process.